Effect of hearing status on visual reliance during postural control performance - Brancaleone, M. P.; Caccese, J.; Talarico, M.; Boucher, L. C.; Merfeld, D.; Grooms, D.; Onate, J. A. (International Journal of Athletic Therapy & Training, 2025)
Athletes who are deaf or hard-of-hearing (D/HoH) have differing postural control performance differences compared with athletes who are hearing; however, no evidence exists regarding their reliance on visual information. Therefore, the purpose of this study was to compare the visual reliance during postural control between athletes who are D/HoH and athletes who are hearing. Athletes who are D/HoH (n = 22) and athletes who are hearing (n = 24) completed the traditional modified clinical test of sensory interaction and balance tasks with the addition of a third visual condition using stroboscopic vision glasses. Independent t tests revealed sway velocity Romberg ratios for eyes closed/eyes open on firm, eyes closed/eyes open on foam (p = .01), and stroboscopic vision/eyes open on foam were different between groups (p < .05 for all). Sway area Romberg ratios were not different (p > .05). Findings may allow health care professionals to gauge recovery from injury in athletes who are D/HoH.